Novel anti-inflammatory activity of epoxyazadiradione against macrophage migration inhibitory factor inhibition of tautomerase and proinflammatory activities of macrophage migration inhibitory factor - Alam, Athar; Haldar, Saikat; Thulasiram, Hirekodathakallu V.; Kumar, Rahul; Goyal, Manish; Iqbal, Mohd Shameel; Pal, Chinmay; Dey, Sumanta; Bindu, Samik; Sarkar, Souvik; Pal, Uttam; Maiti, Nakul C.; et al. (Journal of Biological Chemistry, 2012)
Macrophage migration inhibitory factor (MIF) is responsible for proinflammatory reactions in various infectious and noninfectious diseases. We have investigated the mechanism of anti-inflammatory activity of epoxyazadiradione, a limonoid purified from neem (Azadirachta indica) fruits, against MIF. Epoxyazadiradione inhibited the tautomerase activity of MIF of both human (huMIF) and malaria parasites (Plasmodium falciparum (PfMIF) and Plasmodium yoelii (PyMIF)) non-competitively in a reversible fashion (K-i, 2.11-5.23 mu M). Epoxyazadiradione also significantly inhibited MIF (huMIF, PyMIF, and PfMIF)-mediated proinflammatory activities in RAW 264.7 cells. It prevented MIF-induced macrophage chemotactic migration, NF-kappa B translocation to the nucleus, up-regulation of inducible nitric-oxide synthase, and nitric oxide production in RAW 264.7 cells. Epoxyazadiradione not only exhibited anti-inflammatory activity in vitro but also in vivo. We tested the anti-inflammatory activity of epoxyazadiradione in vivo after co-administering LPS and MIF in mice to mimic the disease state of sepsis or bacterial infection. Epoxyazadiradione prevented the release of proinflammatory cytokines such as IL-1 alpha, IL-1 beta, IL-6, and TNF-alpha when LPS and PyMIF were co-administered to BALB/c mice. The molecular basis of interaction of epoxyazadiradione with MIFs was explored with the help of computational chemistry tools and a biological knowledge base. Docking simulation indicated that the binding was highly specific and allosteric in nature. The well known MIF inhibitor (S, R)-3-(4-hydroxyphenyl)-4,5-dihydro-5-isoxazole acetic acid methyl ester (ISO-1) inhibited huMIF but not MIF of parasitic origin. In contrast, epoxyazadiradione inhibited both huMIF and plasmodial MIF, thus bearing an immense therapeutic potential against proinflammatory reactions induced by MIF of both malaria parasites and human.

Notch1-MAPK signaling axis regulates CD133+ cancer stem cell-mediated melanoma growth and angiogenesis - Kumar, Dhiraj; Kumar, Santosh; Gorain, Mahadeo; Tomar, Deepti; Patil, Harshal S.; Radharani, Nalukurthi N. V.; Kumar, Totakura V. S.; Patil, Tushar V.; Thulasiram, Hirekodathakallu V.; Kundu, Gopal C. (Journal of Investigative Dermatology, 2016)
Functional characterization and understanding of the intricate signaling mechanisms in stem-like cells is crucial for the development of effective therapies in melanoma. We have studied whether melanoma cells are phenotypically distinct and hierarchically organized according to their tumorigenic nature. We report that melanoma-specific CD133(+) cancer stem cells exhibit increased tumor-initiating potential, tumor-endothelial cell interaction, and lung metastasis. These cells are able to transdifferentiate into an endothelial-like phenotype when cultured under endothelial differentiation-promoting conditions. Mechanistically, Notch1 upregulates mitogen-activated protein kinase activation through CD133, which ultimately controls vascular endothelial growth factor and matrix metalloproteinase expression in CD133(+) stem cells leading to melanoma growth, angiogenesis, and lung metastasis. Blockade or genetic ablation of Notch1 and mitogen-activated protein kinase pathways abolishes melanoma cell migration and angiogenesis. Chromatin immunoprecipitation and reporter assays revealed that Notch1 intracellular domain regulates CD133 expression at the transcriptional level. Andrographolide inhibits Notch1 intracellular domain expression, Notch1 intracellular domaindependent CD133-mediated mitogen-activated protein kinase and activator protein-1 activation, and epithelial to mesenchymal-specific gene expression, ultimately attenuating melanoma growth and lung metastasis. Human malignant melanoma specimen analyses revealed a strong correlation between Notch1 intracellular domain, CD133, and p-p38 mitogen-activated protein kinase expression and malignant melanoma progression. Thus, targeting Notch1 and its regulated signaling network may have potential therapeutic implications for the management of cancer stem cell-mediated melanoma progression.

Neem derivatives inhibits tau aggregation - Nalini, Gorantla Vijay; Das, Rashmi; Mulani, Fayaj Alam; Thulasiram, Hirekodathakallu V.; Chinnathambi, Subashchandrabose (Journal of Alzheimer s Disease Reports, 2021)
Tau is a phosphoprotein with natively unfolded conformation that functions to stabilize microtubules in axons. Alzheimer's disease pathology triggers several modifications in tau, which causes it to lose its affinity towards microtubule, thus, leading to microtubule disassembly and loss of axonal integrity. This elicit accumulation of tau as paired helical filaments is followed by stable neurofibrillary tangles formation. A large number of small molecules have been isolated from Azadirachta indica with varied medicinal applications. The intermediate and final limonoids, nimbin and salannin respectively, isolated from Azadirachta indica, were screened against tau aggregation. ThS and ANS fluorescence assay showed the role of intermediate and final limonoids in preventing heparin induced cross-β sheet formation and also decreased hydrophobicity, which are characteristic nature of tau aggregation. Transmission electron microscopy studies revealed that limonoids restricted the aggregation of tau to fibrils; in turn, limonoids led to the formation of short and fragile aggregates. Both the limonoids were non-toxic to HEK293T cells thus, substantiating limonoids as a potential lead in overcoming Alzheimer's disease.